Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1227/00006123-199209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Color-Coded Real-Time Sonography in the Evaluation of Intracranial Neoplasms and Arteriovenous Malformations

Abstract: Transcranial color-coded real-time sonography (TCCS) was performed in 57 patients with primary intracranial brain tumors (n = 49) or arteriovenous malformations (n = 8) to evaluate its diagnostic potential. In 46 patients (81%), lesions could be identified employing this technique. In 7 patients, transcranial ultrasound examination was not feasible because of bone thickness; in the remaining 4 patients, the tumor was indistinguishable from adjacent brain tissue despite sufficient insonation, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 20 publications
2
32
0
1
Order By: Relevance
“…The sensitivity per aneurysm in previous noncontrast TCDS studies has ranged from 0.40 18 in the only previous large prospective study (nϭ203) to 0.89 in a smaller study of 36 patients. 11 Several other small studies have also reported sensitivity in the range of 0.53 to 0.89, 7,9,12,19 although all were in populations with a high prevalence of aneurysms. The difference between sensitivity in the present study and that reported in the early small studies might be due to a number of factors.…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The sensitivity per aneurysm in previous noncontrast TCDS studies has ranged from 0.40 18 in the only previous large prospective study (nϭ203) to 0.89 in a smaller study of 36 patients. 11 Several other small studies have also reported sensitivity in the range of 0.53 to 0.89, 7,9,12,19 although all were in populations with a high prevalence of aneurysms. The difference between sensitivity in the present study and that reported in the early small studies might be due to a number of factors.…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
“…7,9,11 The transnuchal and transorbital routes were not routinely used (some of the patients found these difficult to tolerate), and intravenous echo contrast was not used. Each major intracranial vessel segment was examined systematically with power and anglecorrected spectral Doppler ultrasound.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…US obviates the need for high costs and specialized surgical instruments. However, although standard US B-mode imaging is excellent for tumor localization, little information is provided regarding microcirculation and perfusion dynamics, even when integrated with Doppler sonography [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…TCD can be used to confirm changes in cerebral hemodynamics [5] and has been commonly accepted as a method for evaluation of intracranial arterial stenoses or occlusions and arterial vasospasm after subarachnoid hemorrhage [1,30]. More recently, ultrasonic improvements have led to evaluation for morphologic imaging of the vessels by color-coded real-time sonography [4]. Preliminary reports suggest that TCD readings in the middle cerebral artery (MCA) also may correlate with intracranial pressure (ICP) elevation in patients with severe brain edema and brain death after head injury, and in hydrocephalic infants [13,18,31].…”
mentioning
confidence: 99%